An Appraisal Analysis Of Mood Adjuncts Expressing Assurance And Concession In Discourses Of American Idol And Vietnam Idol - Phan Thị Hồng Mai (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The thesis was done in an effort to investigate and analyze the languages Mood adjuncts expressing assurance and concession in discourses of American Idol and Vietnam Idol. In order to conduct the study, the descriptive analysis with the combination of both qualitative and quantitative research methods was adopted on the basis of the theories of Appraisal and Functional Grammar. The data for the study was built up with 150 samples in English and Vietnamese. The study examined the syntactic and semantic features of Mood adjuncts expressing assurance and concession in discourses of American Idol and Vietnam Idol. In terms of grammatical realization, based on Functional Grammar, the study found that the languages of Mood adjuncts expressing assurance and concession in discourses of American Idol and Vietnam Idol were recognized with their mobility in various positions in the clausal structure or utterance.Their neutral position in the clause is next to the Finite verbal operator, either just before it or just after it. But there are two other possible locations: before the Subject to function as Theme and at the end of the clause as Afterthought in the Clause as Message and Clause as Exchange. Semantically, in the light of Appraisal Theory, the study revealed that Mood adjuncts expressing assurance and concession in discourses of American Idol and Vietnam Idol are speech functional, used to assure and admit the hearers what the speakers say is true. On the basis of the findings, several implications and suggestions on comprehending, translating the language of Mood adjuncts expressing assurance and concession as well as learning and teaching English through language of Mood adjuncts expressing assurance and concession in particular and Appraisal language in general were put forward.